In situ study of radiation stability and associated conduction mechanisms of Nb-Doped TiO2/p-Si heterojunction diode under swift heavy ion irradiation - Gautam, Subodh Kumar; Singh, Jitendra; Singh, Ram Gopal; Gautam, Naina; Trivedi, Priyanka; Singh, Fouran (IEEE Transactions on Electron Devices, 2019)
In situ current-voltage characteristics of Nb-doped TiO2/p-Si-based heterojunction diode have been studied under dense electronic excitations of 84-MeV Si6+ ions. The diode parameters such as ideality factor (eta), barrier height (phi(B)), reverse saturation current (J(s)), and series resistance (R-s) are found to be a strong function of ion irradiation fluence. The observed anomalies of fluence dependence of barrier height and ideality factor are explained in terms of irradiation-induced created defects complexes, modification of interface states and structural properties of Nbdoped-TiO2 (NTO) layer. Several mechanisms suchas barrier height inhomogeneity, donor defects-induced enchantment in n-NTO layer conductivity, and various current conduction mechanisms involved at different voltage ranges are discussed as a function of fluence with the help of constructed energy band diagram. Such in situ studies on n-NTO/p-Si heterojunction diode under radiation harsh environment are very appropriate for the better understanding of heterojunction interface properties and make it suitable for use in aerospace industry and nuclear reactors.
Keywords: Barrier height tuning; n-NTO/p-Si heterojunction; radiation stability of devices; secondary electron irradiation; space-charge limited current